2017
DOI: 10.1080/08820538.2017.1353809
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking Complications

Abstract: Corneal cross-linking was approved by United States Food and Drug Administration for the treatment of progressive keratoconus in April 2016. As this approach becomes more widely used for the treatment of keratoconus and post-laser in situ keratomileusis (LASIK) ectasia, the medical community is becoming more familiar with potential complications associated with this procedure. This article aims to review the reported complications of collagen cross-linking for the treatment of keratoconus and post-LASIK ectasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 47 publications
1
35
1
1
Order By: Relevance
“…CXL using classic Dresden's protocol with epithelium removal (conventional CXL) showed long-term efficacy of stabilization and improvement for KC. However, postoperative complications using standard epi-off protocol [2][3][4][5], such as corneal haze, sterile corneal infiltrates, recurrent erosion syndrome, have been reported and should be taken into consideration. To reduce the risk of postoperative complications, epithelium-on(epi-on) protocols assisted by iontophoretic delivery or transepithelial riboflavin were brought into sight and were considered by some researchers to be a better choice.…”
Section: Introductionmentioning
confidence: 99%
“…CXL using classic Dresden's protocol with epithelium removal (conventional CXL) showed long-term efficacy of stabilization and improvement for KC. However, postoperative complications using standard epi-off protocol [2][3][4][5], such as corneal haze, sterile corneal infiltrates, recurrent erosion syndrome, have been reported and should be taken into consideration. To reduce the risk of postoperative complications, epithelium-on(epi-on) protocols assisted by iontophoretic delivery or transepithelial riboflavin were brought into sight and were considered by some researchers to be a better choice.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Adverse events associated with crosslinking such as anterior keratocyte apoptosis, infection, corneal edema, corneal nerve damage, and stromal haze have been reported. 37 , 38 In addition to these postoperative complications, separate studies have also shown that mutations in stromal proteoglycans can lead to random space reductions between adjacent collagen fibrils; formation of larger, more variable collagen fibrils; and corneal opacity. 39 The transformation of keratocytes to activated fibroblasts and myofibroblasts while critical to corneal wound healing is known to be a major contributing factor in the development of corneal haze and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Dresden protocol overcame this through epithelial debridement (“epithelium-off”), allowing diffusion of riboflavin molecules into the stroma. Even though epithelial debridement provides favourable riboflavin penetration, this is associated with risks such as pain, infection, persistent epithelial defects, and corneal melt ( Spoerl et al, 2007 ; Evangelista and Hatch, 2018 ).…”
Section: Maximising Pharmacokinetic Properties Of Riboflavin/ultraviolet-a In the Treatment Of Keratoconusmentioning
confidence: 99%
“…The precise mechanism for herpes simplex virus reactivation after CXL remains unknown. It is postulated that emotional stress, trauma, and exposure to UVA are possible mechanisms of reactivation ( Evangelista and Hatch, 2018 ).…”
Section: Contraindications and Complicationsmentioning
confidence: 99%